Unveiling the metabolic transformation of Astragalus membranaceus through probiotic fermentation and its impact on growth and gut health in common carp (Cyprinus carpio) - Hongtao Shi; Mengfei Ma; Baocai Ma; Xiufen Wang; Jianxun Guo; Xianqian Jiao; Yueying Wang; Heping Li; Kai Zhong; Guoyu Yang; Huanling Wang; Yingqian Han (Aquaculture Reports)
This study investigated the compositional changes in Astragalus membranaceus after fermentation with Lactobacillus plantarum and evaluated the impact of the fermented products on the growth and gut health of common carp (Cyprinus carpio). A comprehensive metabolomics analysis revealed that fermentation increased metabolites linked to antioxidant and growth-promoting effects. Over an eight-week period, 180 common carp (6.97 ± 0.07 g) were distributed into three groups: a control group receiving a basal diet, and two experimental groups receiving the same diet supplemented with either a 1 ‰ fermented A. membranaceus (FA) aqueous solution or a stock solution. Fish supplemented with FA showed significantly improved growth metrics and feed conversion ratios compared to the control group. Moreover, FA supplementation improved antioxidant status in the gut and liver, increased crude fat and ash content in muscle tissue, and promoted the proliferation of beneficial gut microbiota associated with nutrient digestion, absorption, and gut health. Administering FA aqueous solution elevated the levels of Proteobacteria, Actinobacteria, Chloroflexi, Bacteroidetes, and Verrucomicrobia, while decreasing Fusobacteria and Tenericutes. The FA stock solution enhanced the presence of Chloroflexi, Bacteroidetes, and Verrucobacteria, while decreasing the presence of Fusobacteria, Proteobacteria, Tenericutes, and Actinobacteria. FA supplementation enhanced gut enzyme activities and upregulated genes associated with tight junctions and immune function. FA supplementation enhanced tissue antioxidants, gut function, and microbiota composition in common carp, leading to improved growth.